Adaptive Reprogramming During Early Seed Germination Requires Temporarily Enhanced Fermentation-A Critical Role for Alternative Oxidase Regulation That Concerns Also Microbiota Effectiveness - Bharadwaj, Revuru (2021)
Plants respond to environmental cues via adaptive cell reprogramming that can affect whole plant and ecosystem functionality. Microbiota constitutes part of the inner and outer environment of the plant. This Umwelt underlies steady dynamics, due to complex local and global biotic and abiotic changes. Hence, adaptive plant holobiont responses are crucial for continuous metabolic adjustment at the systems level. Plants require oxygen-dependent respiration for energy-dependent adaptive morphology, such as germination, root and shoot growth, and formation of adventitious, clonal, and reproductive organs, fruits, and seeds. Fermentative paths can help in acclimation and, to our view, the role of alternative oxidase (AOX) in coordinating complex metabolic and physiological adjustments is underestimated. Cellular levels of sucrose are an important sensor of environmental stress. We explored the role of exogenous sucrose and its interplay with AOX during early seed germination. We found that sucrose-dependent initiation of fermentation during the first 12 h after imbibition (HAI) was beneficial to germination. However, parallel upregulated AOX expression was essential to control negative effects by prolonged sucrose treatment. Early downregulated AOX activity until 12 HAI improved germination efficiency in the absence of sucrose but suppressed early germination in its presence. The results also suggest that seeds inoculated with arbuscular mycorrhizal fungi (AMF) can buffer sucrose stress during germination to restore normal respiration more efficiently. Following this approach, we propose a simple method to identify organic seeds and low-cost on-farm perspectives for early identifying disease tolerance, predicting plant holobiont behavior, and improving germination. Furthermore, the research strengthens the view that AOX can serve as a powerful functional marker source for seed hologenomes.